(untitled) (Jurnal Bahasa, 2015)
This paper will discuss the vocal system of Kabong Malay dialect (DMKb ), which is one of the Malay dialects spoken in Sarawak. Kabong is a small area located in Betong, Sarawak. DMKb is spoken by the Malay community in Kabong which can be regarded as a communication language in Kabong for its dominant role to the local community. Besides the Malay community, other races such as Iban and Chinese also live in this area as a minority. This study identifies the DMKb vowel system, phoneme, allophone, diphthongs, distribution vowel phonemes and minimal pairs. DMKb will be described using the descriptive linguistics developed by Bloomfield and developed by Mario Pei and Robins. The descriptive model by Asmah was also used to analyse the vocal tract of DMKb. Data for this research were obtained from the upstream field study using word lists (citations), domain and association of ideas. Descriptive analysis successfully determined that the eight vowels [a], [e], [«], [E], [i], [o], [] and [ u ] are of the status of distinctive phonemes which in turn indicates that the vowel phonemes in DMKb exceed the vowel phonemes in standard Malay language(BMS). Keywords: descriptive, phonemes, vocal, domain, word list, minimal pairs